2012
DOI: 10.1007/s00428-012-1289-9
|View full text |Cite
|
Sign up to set email alerts
|

Keratin expression in breast cancers

Abstract: Cytokeratin (CK) immunohistochemistry can play an important role in breast carcinoma evaluation. We evaluated the expression of a panel of commonly used CKs in a large cohort of breast cancers and assessed its correlation with other biomarkers and breast cancer subtypes. Expression of CK7, CK8, CK18 and CK19 was observed in more than 90 % of all breast carcinomas in this study, confirming their efficacy in immunohistochemical identification of breast cancer. A combination of CK8 and CK7 gave the highest sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 35 publications
4
63
0
1
Order By: Relevance
“…We have demonstrated that CK5/6 gave a higher detection rate than CK14 for BLBC. 61 The cutoffs for its positivity in the literature range from any positive cytoplasmic staining to 20% of tumor cells. 62 EGFR EGFR, also known as HER1, is a member of the HER family.…”
Section: Ck5/6mentioning
confidence: 99%
“…We have demonstrated that CK5/6 gave a higher detection rate than CK14 for BLBC. 61 The cutoffs for its positivity in the literature range from any positive cytoplasmic staining to 20% of tumor cells. 62 EGFR EGFR, also known as HER1, is a member of the HER family.…”
Section: Ck5/6mentioning
confidence: 99%
“…IHC expression of CK7, CK8, CK18 and CK19 is observed in more than 90% of all breast carcinomas (14). Expression of CK5/6, CK14 and CK20 correlate with high tumor grade.…”
Section: Cytokeratin (Ck)mentioning
confidence: 99%
“…Cytokeratins make the cytoplasmic intermediate filaments. These filaments can play an important role in breast carcinoma evaluation [15,17]. Despite extensive analysis of expression of individual CKs in breast cancer, only a few studies have been focused on the high molecular weight CK panels [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratins (CKs) constitute the largest intermediate filament protein subgroup and represent a multigene family with more than 20 different types of polypeptides that are divided into acidic type I (CK9-CK20) and basic type II (CK1-CK8) keratins [14]. Several studies focused on CK type I (CK14, CK17, CK18, CK19, CK20) and type II (CK5, CK6, CK7, CK8) abundant expression in breast cancer cells and its experimentally well-established role in cancer biology [15][16][17]. However, expression of CK1, a high molecular weight cytokeratin, has been limited.…”
Section: Introductionmentioning
confidence: 99%